Interrupções no fluxo de trabalho de enfermagem: estudo em unidade de quimioterapia - Bertolazzi, Luana Gaino (2017)
Investigate the nursing staff workflow interruptions concerning the processes and factors involved in their activities, such as: sources and causes of interruptions, and interrupted activities; Measure the frequency and the duration of interruptions experienced by the nursing staff, as well as the total amount of time elapsed to complete the activities. Methods: This is a quantitative, observational, and analytical study carried out at the chemotherapy facility of a teaching hospital from June / 2015 to March / 2016. Study sample was composed of 11 professionals on the nursing staff (nurses; n=8 and licensed practical nurses; n=3) who accepted to have their care activities measured by the study. We used the technique of direct observation and a stopwatch to map and classify each minute of the activities performed by the nursing staff, according to the taxonomy described by Nursing Interventions Classifications, as well as the interruptions that occurred at the time. Throughout an interruption, we registered the time it started and ended, as well as the subject who was producing it and its cause. Results: We observed 106 hours of the nursing staff workflow. We identified 72 activities correlated to 33 interventions found in the taxonomy, which were carried out 4,033 times. The domain “Complex Physiological” concentrated the largest number of nursing activities performed. There were 492 (12.2%) interruptions, especially in the following domains: Complex Physiological (n=228;46.3%) and Health System (n=159;32.4%). Regarding the sources of disruptions, the main cause was the nursing team itself (n=276;55.5%), mainly motivated by the exchange of care information (n=65; 12.8%) and material supplies (n=65;12.8%). Nursing professionals interrupted their activities 4.6 times per hour, on average; registered nurses interrupted their activities 4.9 times per hour and the licensed practical nurses 3.8 times. Without being interrupted, nursing staff activities took 2:16 minutes (SD± 0:27 minutes) to be completed; when the activities were interrupted, the average time rose up to 5:59 minutes (SD±3:01 minutes). Conclusion: Interruptions were a constant during the nursing staff work at chemotherapy facility, including preparation and administration of medications. These interruptions increased the time required to complete nursing activities up to 163.9%, on average. Understanding the interruptions on nursing performance scenarios can provide support to health managers to carry out a reformulation on the structural and working processes. By doing so, health managers can reduce occurrence of interruptions and the negative impacts that may affect the productivity and safety of the patients.